Activity and Ranging Behavior of Leopard Cats (Prionailurus bengalensis) in an Oil Palm Landscape - Silmi, Muhammad; Putra, Kharisma; Amran, Ali; Huda, Mahfud; Fanani, Aldino Fauzil; Galdikas, Birute Mary; Anggara S, Prima; Traeholt, Carl (Frontiers in Environmental Science, 2021)
The leopard cat (Prionailurus bengalensis) is the most widespread feline in Asia. It has been recorded in a range of habitats, including monoculture landscapes, such as oil palm plantations. Here, we report on a study on the presence, home range, activity patterns and diet of the species in an oil palm landscape to assess their viability as biological pest controller of rats. The study took place in United Plantations/PT SSS estate in central Kalimantan, Borneo, Indonesia. From July 2014 to March 2018, we captured 11 leopard cats in purpose-built cage-traps and fitted them with VHF radio-transmitters. They were tracked for a 44 months study period, during which we collected a total of 2.031 GPS locations used for estimating the respective cats’ activities and home-ranges. The cats are strictly nocturnal and prefer to hide and rest in thick bush, primarily consisting of sword-fern (Nephrolepis sp) during day-time, but forage both on the ground and in the palm canopy at night. The average home range (95% FK) for male leopard cats is 1.47 km2 (n = 7; SD = 0.62 km2) with slightly smaller home range for females at 1.29 km2 (n = 4; SD = 0.28 km2). All individuals studied were recorded strictly within the oil palm plantation landscape, although mangrove forest habitat makes up 7% of the greater plantation landscape. In conclusion, leopard cats survive and reproduce well in oil palm habitats and are effective biological controllers of rats that can replace the traditionally used expensive and environmentally polluting chemical rat poisons.